La trilogie européenne de Camille de Toledo: une proposition du "vertige" pour le XXIe siècle - Coutinho, Ana Paula (2017)
Considering the current context of catastrophic visions and melancholic scarcity of propositional writings on Europe, on the world and, in general, on the future of humanity, but also taking into account the «ethical turn» in literature (and the narrativisation of ethics), it seems interesting, and even important, to analyze the "European trilogy" of a young writer such as Camille de Toledo, which includes an essay and two novels - Le Hêtre et le bouleau. Essai sur la Tristesse Européenne (2009), Vies pØtentielles (2011) and Oublier, trahir puis disparaître (2014). I will focus on how the author relates memory and oblivion, as a process of overcoming existential and creative blockages inherited from twentieth century's legacy, as well as on his proposition of "vertigo" taken as a metaphor for a (re)utopian creation.